Pengaruh Transformasi Digital Terhadap Kinerja Pegawai Di Kantor Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Sidenreng Rappang - Ikra Cahyani; Lukman Lukman; Ahmad Mannu Mannu (Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
This research is motivated by the issue of inconsistency in the service time standards at the Office of Population and Civil Registration of Sidenreng Rappang Regency, indicating suboptimal employee performance, particularly in terms of service speed. Digital transformation, as an innovative solution, is expected to enhance the efficiency and effectiveness of public services. This study aims to determine the influence of digital transformation on employee performance. The research employs a quantitative approach with an associative type of study. Data collection techniques include observation, questionnaires, and literature review. The data were analyzed using validity tests, reliability tests, and simple linear regression with the help of IBM SPSS 21.0 software. The results show that digital transformation is rated as "very good" with an average score of 86%, reflecting successful implementation in cataloging, horizontal integration, and vertical integration. Likewise, employee performance is also categorized as very good, with the same average score of 86%, based on indicators such as quality of service, communication, promptness, capability, and initiative. Based on the simple regression test, the value of R = 0.827 and R² = 0.684 indicates that 68.4% of employee performance is influenced by digital transformation, while the remaining 31.6% is influenced by other factors. The t-test results show that digital transformation has a positive and significant effect on employee performance, with a t-count greater than t-table and a significance value of less than 0.001. This study concludes that digital transformation significantly improves the effectiveness, efficiency, and quality of employee performance in public service delivery.